Reinterpretation of the Average Consumer Benchmark considering Recent Developments - Gül Büyükkılıç (İstanbul Hukuk Mecmuası)
In trademark law, the “average consumer” is a benchmark that represents the target audience of a product or service and is considered in cases of trademark registration or infringement. This criterion plays a decisive role in assessing consumer behaviour and perceptions and deciding on the registrability or infringement of a particular trademark. Although the average consumer has been formulated as “a person who is reasonably well-informed and reasonably observant and circumspect” by the doctrine and judicial decisions, it is an undeniable fact that the formulation of the average consumer is far from providing the necessary flexibility to the judiciary in the evaluation of the concrete case, especially today, when electronic commerce is gaining importance, market conditions are changing day by day, and the perception of the consumer has taken a different shape from the traditional understanding. An interdisciplinary approach to the average consumer criterion and the inclusion of survey evidence and public opinion survey evidence regarding actual use and likelihood of confusion within the scope of the global assessment of likelihood of confusion would be beneficial in terms of resolving concrete disputes on a more objective basis.